Increasing the capacity of electrical transmission lines in the post-emergency mode - Omelchuk, A.; Zakolodyazhnyi, V. (Energy and Automation, 2023)
. Automatic switching on of the reserve (AVR) points are used to increase the reliability of power supply to consumers, which are advisable to install in distribution power networks and consumer networks for the power supply of production processes, the technology of which does not allow even short-term interruptions in power supply. The purpose of the research: substantiating the location of the AVR point for mutual redundancy of power transmission lines; determination of the effect of longitudinal capacitive compensation on the transmission capacity in the post-emergency mode; determining the impact of reactive power compensation on the economy of the post-emergency power transmission mode. The article considers a method of increasing the capacity of power transmission in the post-emergency mode, as a result of which an adjacent (reserved) line is connected to one of the working power transmission lines with a voltage of 10 kV using the point of automatic switching on of the reserve (AVR). However, the effectiveness of such redundancy in most cases turns out to be low due to the limited capacity of trunk sections of mutual-reserved lines with smaller cross-sections of wires at the end sections of both mutually-reserved lines, which were built as radials. As a result of such redundancy, there are increased losses of active power and voltage, and, as a result, unacceptable deviation of the voltage in remote nodes of the load of the redundant power transmission line. In order to improve the parameters of the operation mode of power transmission, it is proposed to use devices of longitudinal capacitive compensation and reactive power compensation in the scheme of the AVR point. Key words: redundancy, voltage deviation, capacitor banks, power transmission lines, bandwidth